Note upon Carn nan Bharraich, or Cairn of the Men of Barra, a Burial Mound of the Viking Time on the Island of Oronsay, Argyllshire, with an outline of the Political History of the Western Isles during the latter half of the Ninth Century - Grieve, Symington (Proceedings of the Society of Antiquaries of Scotland, 1914)
The mound was excavated in 1891 and artefacts included an oblong bronze brooch, a portion of a bronze penannular brooch of Celtic form, a portion of a small oval bronze ring, a bead of serpentine, a bead of amber, an iron knife-blade, six fragments of sheet bronze, a quantity of iron rivets or clinker nails and a stone sinker. Two extended skeletons, an adult male and female, were revealed. Further excavation revealed a pair of iron shears. The burial of persons wearing pagan ornaments, on Oronsay, which had for at least between one and two centuries prior to this time been a sanctuary of the early Celtic Church, is worthy of notice. The mound is situated some distance from the Christian Cemetery, but is within the sanctuary. An account of the historical background provides a context for the burials.